2015
DOI: 10.1111/1477-8947.12082
|View full text |Cite
|
Sign up to set email alerts
|

The legacy of migration in response to climate stress: learning from theGilbertese resettlement in theSolomonIslands

Abstract: The long-term threat of sea-level rise to coral atoll and reef island communities in Kiribati, Tuvalu and other nations has raised the possibility of international migration. Historical resettlements in the Pacific may provide valuable insight into the long-term effect of future climate change-related migration on communities. This study evaluates the challenges faced by Gilbertese people resettled from modern-day Kiribati to Ghizo in the Solomon Islands by the British colonial administration in the mid-1900s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…In his eyes, considerations of the cultural links that communities have to their land are thus crucial to successful relocation. Such sentiments align well with similar scholarship in the Pacific regarding climate migration (Barnett & O'Neill, 2012;Campbell, 2012;Donner, 2015;Lazrus, 2012;McNamara & Des Combes, 2015;Monson & Foukona, 2014). To minimize cultural frictions, maintain cultural ties, and center a ni-Vanuatu understanding of land in climate-related resettlement policy, the voices of ni-Vanuatu communities should be sought out and adhered to in this policymaking.…”
Section: Notes From the Field: Recommendations For A Community-informsupporting
confidence: 81%
See 2 more Smart Citations
“…In his eyes, considerations of the cultural links that communities have to their land are thus crucial to successful relocation. Such sentiments align well with similar scholarship in the Pacific regarding climate migration (Barnett & O'Neill, 2012;Campbell, 2012;Donner, 2015;Lazrus, 2012;McNamara & Des Combes, 2015;Monson & Foukona, 2014). To minimize cultural frictions, maintain cultural ties, and center a ni-Vanuatu understanding of land in climate-related resettlement policy, the voices of ni-Vanuatu communities should be sought out and adhered to in this policymaking.…”
Section: Notes From the Field: Recommendations For A Community-informsupporting
confidence: 81%
“…McNamara and Des Combes (2015), who examine a resettlement of a village in Fiji as a 'last resort' measure to sustain livelihoods, and Donner (2015), who draws lessons from the historical resettlement of the Gilbertese people to the Solomon Islands, also corroborate the preferences that Pacific Islanders have had for moving only if other adaptation options are no longer available. When this is the case-when community participation indicates a determined community will to first examine alternative options to migrationsuch decisions must be respected (Constable, 2016).…”
Section: Notes From the Field: Recommendations For A Community-informmentioning
confidence: 77%
See 1 more Smart Citation
“…Research has widely found that populations experiencing involuntary and government‐led relocations – for example development‐forced displacement and resettlement (DFDR) to make way for dams, hydro‐electricity schemes or urban expansion – experience negative outcomes (Maldonado et al, ; Wilmsen and Webber, ). Relocation risks include loss of land, employment, shelter and access to common resources; economic marginalisation; increased morbidity and mortality; food insecurity; disrupted social networks; and negative cultural and psychological impacts (Cernea, ; de Sherbinin et al, ; Donner, ). A commonly referred to example of forced relocation in the Pacific Islands is that of the Banabans who were relocated from Banaba Island to Rabi Island in Fiji (a distance of 3200 km) by the British Government in 1945 to make way for commercial interests around high‐grade phosphate mining (a component of fertilisers).…”
Section: Participation and Informed Consent In Relocation Planning Anmentioning
confidence: 99%
“…Yet interestingly, most studies show that except for communities that already face severe coastal erosion or flooding due to subsidence, until now, other means of adaptation and more sustainable management are often not only possible, but also favoured by island populations before such drastic measures would need to come into play (Betzold, 2015;Barnett & O'Neill, 2012;Lazrus, 2012;Farbotko & Lazrus, 2012;Farbotko, 2005Farbotko, , 2010Shen & Gemenne, 2011;Mortreux & Barnett, 2009;Donner, 2015;Connell, 2016). The results of these studies exemplarily demonstrate that despite the fact that outsiders might view island environments as extremely vulnerable and retreat as a logical consequence, the international dialogue has often failed to include the diversity of local perspectives.…”
Section: Introductionmentioning
confidence: 99%